(untitled) (Terr@ Plural, 2020)
Praça dos Poveiros is a challenging central square in the historic area of Oporto where the omnipresence of stone and heavy traffic on surroundings, with no public equipment, leads to its use for circulation only. The accessibility of the area, which is often unnoticed, could be improved, such as its image, its structure, and the activities on it. The main concept of this intervention proposal is to maintain the passway character and the activities already established, as promoting the most effective use of the square by people of all ages, favoring the interaction between them, making it more attractive and welcoming. It intends to keep the identity of Praça dos Poveiros, modernize it and give it a new atmosphere, with more soul and life.